2021
DOI: 10.1158/1078-0432.ccr-20-3715
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hedgehog Signaling Alters Fibroblast Composition in Pancreatic Cancer

Abstract: Purpose: Pancreatic ductal adenocarcinoma (PDAC) is a deadly disease characterized by an extensive fibroinflammatory stroma, which includes abundant cancer-associated fibroblast (CAF) populations. PDAC CAFs are heterogeneous, but the nature of this heterogeneity is incompletely understood. The Hedgehog pathway functions in PDAC in a paracrine manner, with ligands secreted by cancer cells signaling to stromal cells in the microenvironment. Previous reports investigating the role of Hedgehog signaling in PDAC ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
176
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(186 citation statements)
references
References 62 publications
(127 reference statements)
7
176
3
Order By: Relevance
“…The Hedgehog pathway is abnormally activated in PDAC. [ 113 ] It is evident that Hedgehog signaling pathway stimulates pancreatic stellate cells (PSCs) through direct effects on non‐pancreatic tissues and controls stromal deposition. [ 114 ] A variety of strategies are being considered to inhibit the Hedgehog pathway, which is the pro‐inflammatory stage of PDAC, in order to remove tumor‐stroma.…”
Section: Strategies To Overcome Pdac Barriersmentioning
confidence: 99%
“…The Hedgehog pathway is abnormally activated in PDAC. [ 113 ] It is evident that Hedgehog signaling pathway stimulates pancreatic stellate cells (PSCs) through direct effects on non‐pancreatic tissues and controls stromal deposition. [ 114 ] A variety of strategies are being considered to inhibit the Hedgehog pathway, which is the pro‐inflammatory stage of PDAC, in order to remove tumor‐stroma.…”
Section: Strategies To Overcome Pdac Barriersmentioning
confidence: 99%
“…While transcriptional and phenotypic plasticity among CAFs likely poses some limitations to the feasibility of targeting specific subsets therapeutically, our model enabling targeted ablation of a defined CAF subset raises the possibility that CAF subsets have sufficient functional distinctions that targeting these subsets in preclinical models, to understand their role in PDAC biology, and differentially targeting them therapeutically may indeed be possible. This notion is supported by a recent study employing the potent smoothened antagonist LDE225 to effectively inhibit Hedgehog signaling in mouse models of PDAC (20). This study showed that myCAFs are partially dependent on the Hedgehog pathway, such that LDE225 treatment markedly skewed that PDAC CAF population to reduce myCAFs and increase iCAFs.…”
Section: Discussionmentioning
confidence: 81%
“…The dense ECM in PDAC physically impedes the vasculature and limits delivery of intravenous therapeutic agents (16, 17), and PDAC patients with high levels of stiff fibrosis enriched for matricellular proteins (such as tenascin C) have shortened survival (18). These findings have motivated efforts to develop therapies targeting CAFs, including inhibitors of pathways that regulate their phenotypes (e.g., the Hedgehog pathway) (19, 20) or their immune-modulatory functions (e.g., the CXCL12-CXCR4 axis) (14, 21), and agents targeting the ECM itself (22).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the utility of uridine as a novel nutrient input in PDA cell metabolism and growth, we wondered if uridine is abundant in the tumor microenvironment and what its sources might be. First, we assessed the expression of UPP1 in our published single-cell RNA sequencing data (Steele et al, 2021). UPP1 expression was high in both the tumor epithelial and myeloid cells, which consist mainly of macrophages ( Fig.…”
Section: Resultsmentioning
confidence: 99%